Response of the LMC’s Bar to a Recent SMC Collision and Implications for the SMC’s Dark Matter Profile - Himansh Rathore; Gurtina Besla; Kathryne J. Daniel; Leandro Beraldo e Silva (The Astrophysical Journal)
The LMC’s stellar bar is offset from the outer disk center, tilted from the disk plane, and does not drive gas inflows. These properties are atypical of bars in gas-rich galaxies, yet the LMC bar’s strength and radius are similar to typical barred galaxies. Using N -body hydrodynamic simulations, we show that the LMC’s unusual bar is explainable if there was a recent collision (impact parameter ≈2 kpc) between the LMC and SMC. Pre-collision, the simulated bar is centered and coplanar. Post-collision, the simulated bar is offset (≈1.5 kpc) and tilted (≈8 $\mathop{.}\limits^{\unicode{x000b0}}$ 6). The simulated bar offset reduces with time, and comparing with the observed offset (≈0.8 kpc) suggests the timing of the true collision to be 150–200 Myr ago. Then, 150 Myr post-collision, the LMC’s bar is centered with its dark matter (DM) halo, whereas the outer disk center is separated from the DM center by ≈1 kpc. The SMC collision produces a tilted-ring structure for the simulated LMC, consistent with observations. Post-collision, the simulated LMC bar’s pattern speed decreases by a factor of 2. We also provide a generalizable framework to quantitatively compare the LMC’s central gas distribution in different LMC–SMC interaction scenarios. We demonstrate that the SMC’s torques on the LMC’s bar during the collision are sufficient to explain the observed bar tilt, provided the SMC’s total mass within 2 kpc was (0.8–2.4) × 10 ^9 M _⊙ . Therefore, the LMC bar’s tilt constrains the SMC’s pre-collision DM profile, and requires the SMC to be a DM-dominated galaxy.